Multi-functionality of mesmo: Relationship between function and morphosyntactic ordering - Pezatti, Erotilde Goreti [UNESP]; Peres, Ana Carolina Teixeira[UNESP] (Univ Federal Fluminense, 2022)
This study investigates the use of mesmo in Brazilian Portuguese, taking as theoretical support Functional Discourse Grammar, developed by Hengeveld and Mackenzie (2008). The proposal consists of investigating the multifunctionality of this linguistic item, relating it to the layers proposed by this theoretical model, with the hypothesis that the pragmatic or semantic aspect determines the codification of the Morphosyntactic Level in relation to the position in the syntactic unit (clause or phrase). Therefore, it uses private letters and official letters extracted from the corpus of the Project for the History of Brazilian Portuguese (https://sites.google.com/site/corporaphpb) as a research universe. The objectives are to verify if the different uses are morphosyntactically codified by the position they occupy in the phrase or clause domain. The results reveal that mesmo, at the Interpersonal Level, scopes Subatos, indicating the pragmatic category Emphasis or the pragmatic function Contrast and occupies the initial (P-I) or final (P-F) positions of the phrase; at the Representational Level, it acts either as a nucleus, always occupying the medial position (P-M), or as an identity operator, positioning itself to the left of the phrase (PI+1), or even as a State of Affairs modifier, occupying, in this case, positions adjacent to the verbal word.
Keywords: Functionalism; Word order; Mesmo; Multifunctionality